Functional Properties of Human Auditory Cortical Fields - Woods, David L.; Herron, Timothy J.; Cate, Anthony D.; Yund, E. William; Stecker, G. Christopher; Rinne, Teemu; Kang, Xiaojian (Frontiers in Systems Neuroscience, 2010)
While auditory cortex in non-human primates has been subdivided into multiple functionally-specialized auditory cortical fields (ACFs), the boundaries and functional specialization of human ACFs have not been defined. In the current study, we evaluated whether a widely accepted primate model of auditory cortex could explain regional tuning properties of fMRI activations on the cortical surface to attended and nonattended tones of different frequency, location, and intensity. The limits of auditory cortex were defined by voxels that showed significant activations to nonattended sounds. Three centrally-located fields with mirror-symmetric tonotopic organization were identified and assigned to the three core fields of the primate model while surrounding activations were assigned to belt fields following procedures similar to those used in macaque fMRI studies. The functional properties of core, medial belt, and lateral belt field groups were then analyzed. Field groups were distinguished by tonotopic organization, frequency selectivity, intensity sensitivity, contralaterality, binaural enhancement, attentional modulation, and hemispheric asymmetry. In general, core fields showed greater sensitivity to sound properties than did belt fields, while belt fields showed greater attentional modulation than core fields. Significant distinctions in intensity sensitivity and contralaterality were seen between adjacent core fields A1 and R, while multiple differences in tuning properties were evident at boundaries between adjacent core and belt fields. The reliable differences in functional properties between fields and field groups suggest that the basic primate pattern of auditory cortex organization is preserved in humans. A comparison of the sizes of functionally-defined ACFs in humans and macaques reveals a significant relative expansion in human lateral belt fields implicated in the processing of speech.